Rural populations and health determinants, disparities, and solutions - Crosby, Richard A. 1959-; Wendel, Monica L.; Vanderpool, Robin C. 1975-; Casey, Baretta R. 1953- (San Francisco, Calif. Jossey-Bass, 2012)
"This book provides an overview of rural health in a social disparities framework, providing a strong theoretical and evidence-based rationale for rectifying rural health disparities in the U.S. The book includes a comprehensive examination of critical issues in rural health, and rural health care services, as well as a road map for reducing disparities, building capacity and collaboration, and applying prevention research in rural areas. Also included are a diverse set of case studies designed to illustrate effective strategies for eliminating disparities and preventing public health problems in rural America. This important resource is written for for students, faculty, and researchers in public health, preventive medicine, public health nursing, social work, and sociology" -- Provided by publisher.
Includes bibliographical references and index.
Keywords: Medicine, Rural -- United States; Rural health services -- United States; Rural health -- United States; Health services accessibility -- United States